2005
DOI: 10.1074/jbc.m505023200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Expression and Dimerization of the Endoplasmic Reticulum Oxidoreductase Ero1β

Abstract: Endoplasmic reticulum oxidoreductases (Eros) are essential for the formation of disulfide bonds. Understanding disulfide bond catalysis in mammals is important because of the involvement of protein misfolding in conditions such as diabetes, arthritis, cancer, and aging. Mammals express two related Ero proteins, Ero1␣ and Ero1␤. Ero1␤ is incompletely characterized but is of physiological interest because it is induced by the unfolded protein response. Here, we show that Ero1␤ can form homodimers and mixed heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 38 publications
(57 reference statements)
11
91
0
Order By: Relevance
“…Concomitantly, hydrogen peroxide (H 2 O 2 ) is thought to be produced from oxygen as an electron acceptor (Enyedi et al 2010). Ero1a is expressed broadly in multiple human tissuetypes, whereas Ero1b is well-expressed only in certain tissue-types, such as the pancreas (Dias-Gunasekara et al 2005). Interestingly, Ero1a activity is regulated by the isomerization/reduction of intramolecular disulfide bonds that are exerted by PDI monitoring the redox state of the ER, whereas Ero1b seems to be less tightly regulated and shows higher oxidase activity in vitro (Inaba et al 2010;Tavender and Bulleid 2010a;Wang et al 2011).…”
Section: Er Redox Homeostasismentioning
confidence: 99%
“…Concomitantly, hydrogen peroxide (H 2 O 2 ) is thought to be produced from oxygen as an electron acceptor (Enyedi et al 2010). Ero1a is expressed broadly in multiple human tissuetypes, whereas Ero1b is well-expressed only in certain tissue-types, such as the pancreas (Dias-Gunasekara et al 2005). Interestingly, Ero1a activity is regulated by the isomerization/reduction of intramolecular disulfide bonds that are exerted by PDI monitoring the redox state of the ER, whereas Ero1b seems to be less tightly regulated and shows higher oxidase activity in vitro (Inaba et al 2010;Tavender and Bulleid 2010a;Wang et al 2011).…”
Section: Er Redox Homeostasismentioning
confidence: 99%
“…Limited Proteolysis of Ero1␤G252S and Ero1␤H254Y-We have previously characterized the human Ero1␤ protein and shown that Ero1␤ homodimerises and interacts with PDI by both non-covalent and covalent (disulfide-dependent) interactions (22). Ero1␤ is functionally equivalent to Ero1p (21), and both Ero1␤ and Ero1p bind to PDI (31) and homodimerise (32).…”
Section: Resultsmentioning
confidence: 99%
“…The polyclonal rabbit anti-sera against PDI (28) and Ero1␤ (22) have been described. The mouse monoclonal antibody HA-7 (Sigma), the anti-Myc monoclonal antibody 9B11, and the anti-Myc polyclonal antibody (both Cell Signaling) were commercially available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the shuttling of PDI/Ero1α complexes into the vicinity of mitochondria would result in the higher availability of mitochondrial ATP and FAD, both of which are required for efficient oxidative protein folding (Papp et al 2005). Alternatively, PDI could be re-oxidized by the other Ero1 family member, Ero1β, which is present in non-detectable levels in HEK 293 and HeLa cells (Dias-Gunasekara et al 2005. Since PDI is found abundantly in all domains of the ER, such a mechanism definitely remains a possibility.…”
Section: Discussionmentioning
confidence: 99%